A Settlement in the caatinga: place, representations and identities/Um Assentamento na caatinga: lugar, representações e identidades - Fernando de Souza Cruz; Claudivan Santos Guimarães (Universidade Estadual de Alagoas, 2020)
Place of inspiration for different aspects of popular culture, the region known as backland refers us to representations that sometimes focus on specific characteristics, which gain aspects of generalization of diverse communities and identities: sadness, poverty, suffering, dryness, scarcity and so many others appear as intrinsic to the countrymen and the countrywomen. Looking at the countrymen of the high backlands of Sergipe, who lives in the Florestan Fernandes Settlement, we will try to specify in some points of this location and the human presence, focusing on a possibility of definition in the concept of Place referenced in SANTOS (2008) with emphasis on beings human beings, to then understand how the Identities thought from TÍLIO (2009) are constantly and dialectically reconfigured in the caatinga of Sergipe.